Tingkat Pengetahuan dan Sikap Masyarakat Terhadap Makanan Tradisional Suku Serawai di Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Septri Widiono; Elza Tri Sentia; Apri Andani (Fakultas Pertanian Universitas Jember, 2022)
Traditional food has recently lost its meaning due to the penetration of modern food into rural areas. This study aims to identify the types of traditional food of the Serawai tribe in South Bengkulu Regency, explaining the community's level of cognitive and affective towards its traditional food. The research was conducted by applying in-depth interviews followed by a quantitative survey. Data analysis uses domain analysis technique and Bloom Taxonomy theory. The research found 34 types of traditional food based on their method of presentation. The community cognitive domains of traditional food are categorized as good, but the average value of each level is decreasing. The first four levels of cognitive domains that have good categories are knowledge, comprehension, application and analysis. For the level of synthesis included in the medium, whereas the highest level one, evaluation, is a low category. The affective domains of the community to its traditional food are good category, and the values of each level are also decreasing. Each level of the affective domain which consists of receiving, responding, valuing, organization and characterization, is included in the good category.